PENGARUH FAKTOR DEMOGRAFI TERHADAP PERILAKU PENGGUNAAN KARTU KREDIT - Mariana Ing Malelak; Gesti Memarisa; Njo Anastasia (Inovbiz: Jurnal Inovasi Bisnis, 2016)
Abstract: This study aimed to determine the effect of demographic factors on credit card usage behavior. Demographic factors such as age, gender, income, education, marital status, according to some previous research has significant effect to credit card usage behavior, both it is related with spending activity with credit cards and also the pattern of payments in pay off credit card bills. Sampling was conducted on people  who  live  in  Surabaya, which  has  a  credit  card  either  as  primary and additional card holder. The data collection use questionnaires form, which is distributed to shopping center visitors in Surabaya. Descriptive analysis is used to decribe the demographic factors and credit card usage behavior. SEM-PLS test conducted  to  examine  the  effect  of  demographic factors  such  as  age,  gender, income, education, marital status on credit card usage behavior in Surabaya. The results showed demographic factors (age, income and marital status) significantly affect the credit card usage behavior (in terms of pay off credit card bills) in Surabaya.Keywords: Demographic Factors, Credit card usage behavior.